2019
DOI: 10.1038/s41467-019-11893-4
|View full text |Cite
|
Sign up to set email alerts
|

Engineered triple inhibitory receptor resistance improves anti-tumor CAR-T cell performance via CD56

Abstract: The inhibitory receptors PD-1, Tim-3, and Lag-3 are highly expressed on tumor-infiltrating lymphocytes and compromise their antitumor activity. For efficient cancer immunotherapy, it is important to prevent chimeric antigen receptor T (CAR-T)-cell exhaustion. Here we downregulate these three checkpoint receptors simultaneously on CAR-T cells and that show the resulting PTL-CAR-T cells undergo epigenetic modifications and better control tumor growth. Furthermore, we unexpectedly find increased tumor infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 61 publications
4
77
0
1
Order By: Relevance
“…They were able to show that knock down of all three inhibitory receptors led to the highest cytotoxicity and IFNγ production compared to CAR-T cells with knockdown of one of the receptors or no knockdown. Furthermore, they were able to show that the triple knockdown CAR-T cells up-regulated CD56, which correlated with enhanced infiltration of the CAR-T cells into the tumor tissue [99].…”
Section: Inhibiting Checkpoint Signaling In the Car-t Cellmentioning
confidence: 94%
“…They were able to show that knock down of all three inhibitory receptors led to the highest cytotoxicity and IFNγ production compared to CAR-T cells with knockdown of one of the receptors or no knockdown. Furthermore, they were able to show that the triple knockdown CAR-T cells up-regulated CD56, which correlated with enhanced infiltration of the CAR-T cells into the tumor tissue [99].…”
Section: Inhibiting Checkpoint Signaling In the Car-t Cellmentioning
confidence: 94%
“…Blockade of PD-1 in combination with other immune checkpoint receptors, including TIM-3 and LAG-3, has strong synergistic effects, and boosts effector functions of CAR T cells [35,36]. The high efficacy of this combinatorial approach suggests that TIM-3 and LAG-3 pathways have non-redundant effects that synergize with PD-1 signaling to dampen antitumor responses in dysfunctional CAR T cells.…”
Section: Tim-3 and Lag-3mentioning
confidence: 99%
“…Hamieh et al ( 71 ) found that the CD19 antigen is transferred to CAR T-cells from malignant cells by trogocytosis, which not only leads to escape of the CD19 antigen, but also causes CAR T cells to kill each other and accelerates the depletion of T cells. To weaken mutual killing, CAR T cells gradually express and activate T cell-inhibiting molecules such as programmed cell death protein-1, lymphocyte activation gene-3, and T-cell immunoglobulin and mucin domain 3, leading to the immune escape of tumors ( 71 73 ). Similar experiments performed on CD22-CAR T cells, co-cultured with various cell lines such as SUP-B15 and Raji, and primary tumor cells from patients, also showed similar results that is CAR-induced trogocytosis was observed ( 71 , 74 , 75 ).…”
Section: Recurrence After Car T-cell Therapymentioning
confidence: 99%